Influenza-Induced Rhabdomyolysis in a Patient With Undiagnosed Light Chain Amyloidosis - Jordan Nunnelee; Ashley Egan (Annals of Internal Medicine: Clinical Cases)
This article explores a case of severe rhabdomyolysis in a 51-year-old woman with an influenza A infection. Investigating the cause of rhabdomyolysis is crucial to preventing recurrence. In this case, the patient was found to have underlying light chain amyloidosis with muscle involvement. When a patient presents with severe rhabdomyolysis, it is important to perform frequent physical examinations to assess for advanced muscle edema which can lead to compartment syndrome, as early diagnosis and intervention are paramount to salvaging affected limbs.